Technology, AI, and operational security in banking : mastering cybersecurity and tech risk management - Young, Richard Gwashy (Routledge/Productivity Press, 2026)
In today's rapidly evolving digital landscape, banks are not only financial institutions but also technology-driven enterprises. As banking operations migrate to digital platforms, cyber threats targeting financial institutions have become more sophisticated and relentless.